THE CONCEPT OF MANAGEMENT OF LEARNING MKWU PAI BASED ON MULTICULTURAL COMPONENTS - Iwan Hermawan; Uus Ruswandi; Mohamad Erihadiana (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
AbstractMulticulturalism means cultural diversity or cultural heterogeneity. It is undeniable that students who enter tertiary institutions come from different regions with different ethnicities, different cultural cultures which can be one of the problems that interfere in the learning process. The naming of different people as mentioned by Allah in the Qur'an seems to be a commandment that must be completed by humans themselves using scientific knowledge. Multicultural Education is habituation or cultural education that provides opportunities for all students regardless of gender, social class, ethnicity, race, ethnicity, religion, and culture. In the Qur'an, several verses explain multiculturalism, including in the QS. Al-Hujurat: 13, Q.S. Ar-Rum: 22. The goals of multicultural education are basically in harmony with character education which leads to one goal, namely good behavior or moral values as the main goal of the Islamic religion is revealed on earth. As a reference in implementing multicultural education, a learning management concept is needed based on the components or important elements that exist in a system to process the achievement of expected goals, namely 1) Strengthening similarities rather than differences, 2) Mutual trust and mutual understanding, 3) Tolerance of differences, 4) Discussion is not imposing opinion.Keywords: Management, Learning, Component, Eduacation, multicultural.AbstrakMultikultural bermakna keragaman kultur atau heterogenitas kebudayaan. Tidak dapat dipungkiri bahwa mahasiswa yang masuk pada perguruan tinggi berasal dari berbagai daerah yang berbeda suku, berbeda kultur budayanya yang dapat menjadi salah satu permasalahan yang mengganggu dalam proses pembelajaran. Penamaan manusia yang berbeda-beda sebagaimana yang disebutkan Allah dalam Al-Qur’an seolah menjadi sebuah perintah yang harus diselesaikan oleh manusia itu sendiri dengan cara berilmu pengetahuan. Pendidikan Multikutural adalah pendidikan pembiasaan atau pembudayaan yang memberikan kesempatan pada semua mahasiswanya tanpa memandang jenis kelamin, kelas sosial, ras, suku, agama, dan budayanya. Dalam Al-Qur’an terdapat beberapa ayat yang menjelaskan tentang multikultural, antara lain terdapat dalam Q.S. Al-Hujurat: 13, Q.S. Ar-Rum: 22. Tujuan pendidikan multikultural ini pada dasarnya selaras pendidikan karakter yang bermuara pada satu tujuan yaitu pada perilaku yang baik atau akhlak karimah sebagaimana pokok tujuan agama Islam diturunkan dimuka bumi ini. Sebagai acuan dalam menerapkan pendidikan multikultural tersebut diperlukan sebuah konsep pengelolaan pembelajaran berdasarkan pada komponen-komponen atau unsur-unsur penting yang ada pada suatu sistem untuk memproses pencapaian tujuan yang diharapkan, yaitu 1) Memperkuat persamaan daripada perbedaan, 2) Saling percaya dan saling pengertian, 3) Toleransi terhadap perbedaan, 4) Berdiskusi bukan memaksakan pendapat.Kata Kunci: Pengelolaan, Pembelajaran, Komponen, Pendidikan, Multikultural